Analisis Keefektifan Kalimat dalam Pemberitaan Kasus Perselingkuhan Selebritas pada Rubrik DetikHot - Faizatul Khoiriyah; Miftahul Jennah; Nanda Berlian Dwi Maulita; Mohamad Afrizal (Student Research Journal, 2026)
The aim of this study is to describe the ineffectiveness of sentences in reports on celebrity infidelity in the DetikHot section of the Detik.com online media. The study uses a qualitative approach with a descriptive method because it focuses on analysing linguistic phenomena in news texts. The data source for the study was the sentences in the news articles about celebrity infidelity, which were selected using the purposive sampling technique. Data were collected using the documentation method by reading, noting and classifying data based on the criteria for effective sentences. Data analysis was conducted through the stages of data reduction, data presentation, and conclusion drawing. The results of the study show that there is still a lot of ineffective language use in DetikHot reports, such as wordiness in the phrase 'Masalah yang menyeret nama selebgram Azizah Salsha masih terus bergulir', unclear sentence structure in the phrase 'demi pengakuan suami selingkuh', and the use of non-standard words in the phrase 'bikin heboh'. It was also found that there was the use of illogical sentences and the incorrect choice of words, which caused the information to become ambiguous and less effective. The most common errors were wordiness and unclear sentence structure. This study shows that the quality of journalistic language in online media still needs to be improved to ensure that the information conveyed is clearer, more concise, logical, and easier for readers to understand.